Clinical oncology and error reduction - Surbone, Antonella; Rowe, Michael, 1947- (Wiley-Blackwell, 2015)
"Clinical Oncology and Error Reduction is the first single-source reference to address the vital topics of recognizing, preventing, and responding to medical errors in clinical oncology.-Filled with practical information for immediate clinical application -Covers topics such as patient safety, error prevention, quality improvement, errors disclosure and apology, and the impact of errors on patients and doctors -Each chapter contains special 'take home' points that highlight issues of particular clinical relevance and application -Prepared by an expert, multidisciplinary, international team of physicians, nurses, researchers, hospital administrators, bioethicists, patients and patient advocates"--Publisher's description